2020
DOI: 10.1088/1361-648x/ab9c5b
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic hopping-pinning scenarios in lithium niobate based on atomistic models: different kinds of stretched exponential kinetics in the same system

Abstract: Based on a model of coupled processes with differently time-dependent decay kinetics we present a critical review on photoluminescence (PL) and transient absorption (TA) experiments in undoped and Mg or Fe-doped LiNbO 3 , together with a comprehensive interpretation of visible radiative and parallel non-radiative decay processes on timescales ranging from 50 ns up to minutes. Analogies and peculiarities of the kinetics of mobile self-trapped and pinned excitons are investigated and compared with those of hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…[66][67][68] In addition, the PL intensity decay profiles are clearly nonexponential for both TCPE-FA(50) and TCPE-FA(200) (SI Figures S40) and can be fitted to a stretched exponential indicative of a trapping model for the excitations (SI Figure S41, see SI Section 7 for details). 69 In this model, excitation hopping samples various sites in the MOF lattice, where it will eventually relax radiatively or get trapped at a defect site and decay non-radiatively. Overall, the PL data confirm that the green to blue fluorescence shift observed in conjunction with the phase transition from Form 1 to Form 2 arises from the broadened density of emitting states and enhanced dynamic spectral diffusion in Form 2 compared to Form 1.…”
Section: Resultsmentioning
confidence: 99%
“…[66][67][68] In addition, the PL intensity decay profiles are clearly nonexponential for both TCPE-FA(50) and TCPE-FA(200) (SI Figures S40) and can be fitted to a stretched exponential indicative of a trapping model for the excitations (SI Figure S41, see SI Section 7 for details). 69 In this model, excitation hopping samples various sites in the MOF lattice, where it will eventually relax radiatively or get trapped at a defect site and decay non-radiatively. Overall, the PL data confirm that the green to blue fluorescence shift observed in conjunction with the phase transition from Form 1 to Form 2 arises from the broadened density of emitting states and enhanced dynamic spectral diffusion in Form 2 compared to Form 1.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, only an asymmetric band near 1 eV due to a Mg Li -assisted Nb 4+ Nb polaron was found as a result of reduction (see spectrum (b) of Figure 9 in [45]; it should be noted that the decomposition of this band given in the bottom part of the same figure is incorrect, because trace (d) is already an unphysical difference-band obtained earlier by the comparison of Nb 4+ Nb and Nb 4+ Li bands in crystals above and below the photorefractive threshold, respectively. Apart from this controversy and the unconfirmed assignations to vacancy centers, the results in [45] proved to be highly reliable (see also [46])). The crystal used was beyond the photorefractive threshold where no Nb Li antisites are present; part of the Mg 2+ ions already form self-compensating complexes on both Li and Nb sites, whereas other Mg 2+ Li ions may still be charge-compensated by Li vacancies [47].…”
Section: Defect Generation In Cln By Thermal Reductionmentioning
confidence: 98%
“…Various kinds of radiation, including two-photon absorption [26], X-rays [26,32], Co 60 γrays [48], and higher energy electrons up to 1.7 MeV [30] have been used; along with Nb 4+ Li polarons having an EPR fingerprint and an absorption band at ~1.7 eV, O − hole polarons (also small) preferably trapped at lithium vacancies were also formed, having another EPR fingerprint and an absorption band near 2.5 eV (see Figure 2), fortuitously coinciding with that of bipolarons. In undoped LiNbO 3 , Nb 4+ Li polarons become mobile at temperatures between 100 and 150 K and recombine with the trapped holes [26,32] in a non-radiative process [46]; therefore, the original state of the crystal is restored. Arizmendi et al [32] also reported on the presence of a further smaller band at ~3.2 eV, ascribed to the same trapped-hole polarons in the X-irradiated crystals (again coinciding with similar structures in trapped-electron spectra).…”
Section: Defect Generation In Cln By Ionizing Irradiation At Low Temp...mentioning
confidence: 99%
See 1 more Smart Citation
“…The transient near infra-red absorption in LN is primarily due to small polarons [6,28]. Other optical phenomena are also associated with self-trapped charge carriers and excitons [29][30][31][32][33] We explore the transient absorption from 10 −7 to 10 5 s for temperatures between 45 K and 225 K. A simple model enables us to relate the observed decay rate of the absorption to the temperature-dependent small-polaron jump rate. Analysis of the small-polaron jump rate through the observed temperature range yields plausible estimates of the activation energy for small-polaron hopping and distinctively, the characteristic atomic-vibration frequency.…”
Section: Introductionmentioning
confidence: 99%